2017
DOI: 10.3390/ma10040333
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Feasibility and Forming Properties of Cu-4Sn in Selective Laser Melting

Abstract: Copper alloys, combined with selective laser melting (SLM) technology, have attracted increasing attention in aerospace engineering, automobile, and medical fields. However, there are some difficulties in SLM forming owing to low laser absorption and excellent thermal conductivity. It is, therefore, necessary to explore a copper alloy in SLM. In this research, manufacturing feasibility and forming properties of Cu-4Sn in SLM were investigated through a systematic experimental approach. Single-track experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 22 publications
0
26
0
2
Order By: Relevance
“…Besides, with regard to the equipment factor, the common SLM machines were SLM Solution (Lubeck, Germany), Phenix (Riom, France), EOS (Planegg, Germany), Concept Laser (Lichtenfels, Germany), Renishaw (London, UK), Realizer (Borchen, Germany), and Trumpf (Munich, Germany), which are used in previous studies. Ahmadi et al used Phenix to study the computational framework by SLM of 316L [ 16 ]; Suryawanshi et al used Concept Laser to study the effects of scanning strategy on mechanical properties [ 36 ]; and Mao et al used EOS to study the manufacturing feasibility of forming Cu-4Sn new material [ 37 ]. In this experiment, the use of Renishaw is different from the previous three devices, which split the scanning speed into exposure time and point distance, called ‘’spot-to-spot formation’’, as shown in Figure 2 b.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, with regard to the equipment factor, the common SLM machines were SLM Solution (Lubeck, Germany), Phenix (Riom, France), EOS (Planegg, Germany), Concept Laser (Lichtenfels, Germany), Renishaw (London, UK), Realizer (Borchen, Germany), and Trumpf (Munich, Germany), which are used in previous studies. Ahmadi et al used Phenix to study the computational framework by SLM of 316L [ 16 ]; Suryawanshi et al used Concept Laser to study the effects of scanning strategy on mechanical properties [ 36 ]; and Mao et al used EOS to study the manufacturing feasibility of forming Cu-4Sn new material [ 37 ]. In this experiment, the use of Renishaw is different from the previous three devices, which split the scanning speed into exposure time and point distance, called ‘’spot-to-spot formation’’, as shown in Figure 2 b.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the LPBF of copper alloys is being explored, leading to major challenges due to the high thermal conductivity of the powder, poor absorption of laser wavelengths in the range of ≈1070 nm found in standard LPBF machines, and balling (e.g., Reference [ 6 , 7 ]). As a consequence, densities for LPBF copper alloys achieved with common 200–400 W lasers are inferior to those obtained using EBM; the latter being in the range of 93.7% for Cu-4Sn [ 8 ] to 97.9% for Cu-Cr-Zr-Ti [ 9 ] and from 97.65% [ 10 ] to 99.5% [ 11 ] or even 99.8% [ 12 , 13 ] for CuCr1Zr. On LPBF machines with a non-standard high-powered laser, even pure copper powder can be processed: e.g., a density of 96.6% was achieved using an 800 W laser power [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 12 ] explored the relations between laser energy density and the densification behavior of 3D-printed AlSi 10 Mg alloys, and the results showed that laser energy density has a significant effect on the forming of defects which could lead to poor mechanical properties of the as-printed parts. Mao et al [ 13 ] studied the statistical influences of process parameters, and their results revealed that laser power has the strongest effect on the relative density and Vickers hardness of 3D-printed Cu-4Sn parts. Zhang et al [ 14 ] indicated that a laser energy density over 340 J/mm 3 can result in dense 3D-printed parts of wrought Al-Cu-Mg alloys.…”
Section: Introductionmentioning
confidence: 99%